(untitled) (Pokhara Engineering College Journal, 2026)
This study investigates the effects of thatch content on the characteristics of soil-cement bricks, offering valuable insights into thatch’s potential application as an alternative to binder. Compressive strength, water absorption and cost analysis are the three primary research areas. The favorable effect of thatch as a binder on brick strength is demonstrated by the results, which indicate a considerable increase in compressive strength as thatch content rises in the 0-1% range. According to the Nepal National Building Code (NBC 109: 1994), hand-made bricks may absorb up to 25% of the total weight, but the average water absorption for all percentage mixes is still 23% overall, indicating the possibility of improved water resistance. A cost study further validates the economic viability of the soil-cement bricks, with production costs ranging from NRs 13 to 14, suggesting potential profitability for manufacturers. Collectively, our findings show the feasibility and advantages of use thatch as an alternative binder in the production of soil-cement bricks, offering the construction industry a cost-effective and sustainable choice.